The Role Of The Teacher In The Implementation Of Character Education To Overcome The Problem Of Bullying In Elementary Schools - Khairun Nisa; Ai Sutini; Dinie Anggraeni Dewi (JHSS (JOURNAL OF HUMANITIES AND SOCIAL STUDIES), 2023)
This research examines the role of the teacher in overcoming the problem of bullying in schools through the implementation of character education. The research used in this research is a qualitative research which is described descriptively. Various sources were processed in this study such as books, research results, journals, and research articles. In this study, it was explained that bullying is a vital problem and must be resolved immediately in Indonesia. This is because there are no positive benefits to be gained from this bullying behavior. From this research, it is also known that there are several types, factors, and impacts or effects felt by students as a result of bullying behavior that is carried out. These three aspects can be a guide for teachers to analyze and formulate strategies to solve this problem, one of which is through the application of character education. The importance of teachers in applying moral values; to shape the character of students, especially students of elementary school age, is because, at this age, students easily imitate the behavior and actions they see without knowing exactly what is wrong. So it is very important guidance and direction given by teachers and parents in this implementation process. Therefore, in its implementation, teachers and parents must work together so that character-building through the application of character values can be realized.